Freedom of Press in Myanmar (Journal of Advanced Research in Social Sciences, 2021)
Every person has to enjoy freedom of expressing their opinion and information and they also have the duties to refrain from affecting the right and reputation of other persons. Since it is not an absolute right, the person who practices the right to freedom of press needs to respect the rights and reputations of others. This paper used a qualitative approach by reviewing relevant literature such as international legal instruments, domestic laws and reports regarding freedom of expression. This research mainly based on primary and secondary resources because the required information is obtained from Universal Declaration of Human Rights (UDHR), International Covenant on Civil and Political Rights (ICCPR), General Comment No.34, Johannesburg Principles on National Security and some Myanmar laws such as the Constitution of the Republic of the Union of Myanmar, the Telecommunication Law 2013, the News Media Law 2014, the Official Secrets Act 1923 and the Unlawful Association Act 1908. Although Section 354(a) of the Constitution of the Republic of the Union of Myanmar provides that every citizen has a right to express and publish freely their convictions and opinions, many people including journalists and news media men can be prosecuted under the provisions of the existing laws. Thus, when many people posted information in their own pages, they have been charged with the provisions of the existing laws. Therefore, the existing laws in Myanmar which contain restricted provisions for freedom of press should be repealed or amended and new laws should be enacted in line with the International Human Right standards.